Muppet Treasure Island - Henson, Brian; Juhl, Jerry; Thatcher, Kirk R.; Hart, James V.; Baker, Martin G.; Curry, Tim.; Bishop, Kevin, 1980-; Connolly, Billy; Goelz, Dave.; Whitmire, Steve, 1959-; Nelson, Jerry, 1934-2012.; Mann, Barry; et al. (Burbank, CA : Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2005)
When young Billy comes to possess a secret treasure map, he sets sail with mild-mannered Capt. Smollet and a host of assorted Muppets and humans in search of the wealth. Their adventure is filled with songs, wacky humor, and irreverent silliness.
Title from container.
"Kermit's 50[th] anniversary."--Container.
Based on the novel Treasure Island / by Robert Louis Stevenson.
Videodisc release of the motion picture produced in 1996.
Special feature: Pepe Profiles presents - Fozzie Bear : a long day's journey into night clubs.
Aspect ratios: 1.85:1, enhanced for 16x9 televisions; 1.33:1.
Keywords: Stevenson, Robert Louis, -- 1850-1894 -- Film adaptations; Muppets (Fictitious characters) -- Drama; Treasure Island (Imaginary place) -- Drama; Pirates -- Drama; Film adaptations; Swashbuckler films; Feature films; Adventure -- Feature; Action and adventure films; Adventure films; Video recordings for the hearing impaired